Penelitian Bibliometrik tentang Keberagaman Agama di Indonesia - Destia Anjani; Busro Busro (Gunung Djati Conference Series, 2023)
Indonesia is one of the countries that is known to have several religions in it, with which the diversity of religions in Indonesia is such an interesting discussion that many studies on the subject. The article will focus on mapping using a bibliometric analysis obtained on glaucoma. Based on that database, studies on religious diversity in Indonesia are grouped in four categories. The first field of study, the two research developments of the trfinal nine years, the three dominating researchers, the four place journal publications. Based on that data, the data of the article that has been published by 6,216 journals in 22 different fields is found.